Early Verb Learning: How Do Children Learn How to Compare Events?. Issue 1 (1st January 2016) - Childers, Jane B.; Parrish, Rebecca; Olson, Christina V.; Burch, Clare; Fung, Gavin; McIntyre, Kevin P.
Abstract : An important problem verb learners must solve is how to extend verbs. Children could use cross-situational information to guide their extensions; however, comparing events is difficult. In 2 studies, researchers tested whether children benefit from initially seeing a pair of similar events ("progressive alignment") while learning new verbs and whether this influence changes with age. In Study 1, 2.5- and 3.5-year-old children participated in an interactive task. Children who saw a pair of similar events and then varied events were able to extend verbs at test and differed from a control group; children who saw 2 pairs of varied events did not differ from the control group. In Study 2, events were presented on a monitor. Following the initial pair of events that varied by condition, a Tobii x120 eye tracker recorded 2.5-, 3.5-, and 4.5-year-olds' fixations to specific elements of events (areas of interest) during the 2nd pair of events, which were the same across conditions. After seeing the pair of events that were highly similar, 2.5-year-olds showed significantly longer fixation durations to agents and to affected objects as compared with the all-varied condition. At test, 3.5-year-olds were able to extend the verb, but only in the progressive alignment condition. These results are important because they show children's visual attention to relevant elements in dynamic events is influenced by their prior comparison experience, and they show that young children benefit from seeing similar events as they learn to compare events to each other.